High‐Speed Solar Wind Imprints on the Ionosphere During the Recovery Phase of the August 2018 Geomagnetic Storm - Dexin Ren; Jiuhou Lei; Su Zhou; Wenbo Li; Fuqing Huang; Xiaoli Luan; Tong Dang; Yu Liu (Space Weather)
Abstract The low‐latitude ionospheric TEC observed by the Beidou geostationary satellite showed large enhancement during 27–30 August 2018 of the storm recovery phase. The cause of the positive ionospheric storm during the recovery phase has yet to be resolved. In this study, multiple observations, including aurora, high‐latitude convection, potential, and the TEC maps, were used to study the contributions from the high‐speed solar wind to the ionosphere during the recovery phase of the storm. It was found that the high‐speed solar wind was effective in modulating the intensity and the size of the auroral oval, high‐latitude convection, and potential pattern. The Thermosphere Ionosphere Electrodynamics General Circulation Model generally reproduced the observed evolution of the ionosphere at high latitudes during the recovery phase of the storm, and it was used to quantitatively investigate the effects of the high‐speed solar wind on the recovery phase ionosphere. The results suggested that the high‐speed solar wind caused increase of TEC at auroral oval was about 2 TECU. The high‐speed solar wind, combined with oscillating interplanetary magnetic field Bz, led to the enhancement of the low‐latitude prompt penetrating electric fields and increased the low‐latitude TEC of about 2 TECU. Therefore, the high‐speed solar wind was a possible driver to the ionospheric positive storm during the recovery phase, but the causes for the more than 10‐TECU enhancement at low and middle latitudes during the recovery phase of this event are unknown.